Plasmacytoma of the ovary - Elamouri, Jamila; Shaffouh, Adel; Torjman, Fairouz (Ibnosina Journal of Medicine and Biomedical Sciences, 2021)
Extramedullary plasmacytoma is a rare plasma cell neoplasm that involves the ovary very rarely. Here, I report a case of primary ovarian plasmacytoma in a 42-year-old patient. The patient presented with abdominal distention, and workup showed a left ovarian mass (6.5 cm × 8 cm) with marked ascites. The patient had a hysterectomy with bilateral salpingo-oophorectomy. Histopathologic, immunohistochemical, bone marrow examination, and other relevant examinations established the diagnosis of primary ovarian plasmacytoma with kappa light chain restriction. No evidence of malignancy in the omentum and ascitic fluid was detected. The patient did not need postoperative chemotherapy or radiotherapy, and 6-month follow-up was uneventful. Due to the scarcity of information on these extremely rare tumors with abdominal masses, the diagnosis should be considered if complete surgical resection is achieved and no evidence of multiple myeloma is found.
Keywords: Extramedullary plasmacytoma; extramedullary plasmacytoma; ovary; plasmacytoma; primary neoplasm